Can Do or Can't Do? Benchmarks for Course Design - Ilangakoon, S.R. (University of Colombo, 2015)
Language change has taken place as part of changing social structures. These changes have influenced the teaching contexts of these societies. Sri Lankan history shows how the changing political scenario and language policy of the country (Gunesekera 2005) had impacted education and the language used. ,Today, employers demand improved English language competency from undergraduates in state universities. To achieve this goal, the University Test of English (UTEL) benchmarks were designed as "can do statements" that indicate what students should be able to perform in reading, writing, speaking and listening. Universities need to develop their language curriculum based on the benchmarks and ensure that students reach band 5 of the benchmarks. The objective of the study is to ascertain the relevance of the benchmark abilities at band 5 to be used as a policy requirement of undergraduate language skills. The teaching material used in the Faculty of Arts was scrutinized to see the course alignment with the benchmarks. A questionnaire was administered to around 100 1s t year and 2 n d year students of the Faculty of Arts. However, only 58 responses were returned. Views of ten teachers were obtained to find out their views on the materials taught at band 5. Students and teachers found the currently taught material useful. Students indicated that they wished to improve their ability in spoken English, grammar, letter writing, vocabulary, answering assignments, using case studies, reading, and CV writing. Facing job interviews, handling telephone conversations, speaking and listening activities were the real world abilities they wished to master. Seventy percent of the students felt confident in using English after the completion of the course. Teachers felt that students need activities and feedback to improve writing skills. Reading and vocabulary skills should be developed. Serious concern was expressed over the grammar taught at both band 4 and 5. Furthermore, time and opportunities for language learning should be increased to make any significant improvement in the students' level of language competency and bring about a positive change in their language competency.
Keywords: Benchmarks, Language competency, Undergraduates